Perbaikan Kawasan Bantaran Sungai Gelis di Desa Ploso Kecamatan Jati Kabupaten Kudus dengan Teknologi Vertikultur - Endang Dewi Murrinie; Hendy Hendro Hadisridjono; Nindya Arini (Universitas Muria Kudus, 2021)
Ploso Village, Jati Subdistrict is one of the villages around the Gelis watershed, which is quite dense and some of the residents have a business of making tofu and raising cattle and goats. So far, the people of Ploso Village are not familiar with verticulture technology by utilizing household waste and industrial waste. The purpose of community service activities is to introduce verticulture technology by utilizing inorganic and organic waste around the Gelis Riverbanks, Ploso Village, Jati District, Kudus Regency. Through community service activities, it is hoped that it can prevent and increase public awareness not to throw garbage along the Gelis River. The result of community service activities in Ploso Village is that the community understands and can practice verticulture technology by utilizing inorganic waste as a container for verticulture planting and organic waste for materials for making planting media.